Reducing the burden of injury : advancing prevention and treatment - Bonnie, Richard J.; Fulco, Carolyn; Liverman, Catharyn T. (National Academy Press, 1999)
Injuries are the leading cause of death and disability among people under age 35 in the United States. Despite great strides in injury prevention over the decades, injuries result in 150,000 deaths, 2.6 million hospitalizations, and 36 million visits to the emergency room each year. Reducing the Burden of Injury describes the cost and magnitude of the injury problem in America and looks critically at the current response by the public and private sectors, including: Data and surveillance needs; Research priorities; Trauma care systems development; Infrastructure support, including training for injury professionals; Firearm safety; and, Coordination among federal agencies. The authors define the field of injury and establish boundaries for the field regarding intentional injuries. This book highlights the crosscutting nature of the injury field, identifies opportunities to leverage resources and expertise of the numerous parties involved, and discusses issues regarding leadership at the federal level.